Skull X-Ray Assessment of Head Injuries: A Decision Analytic Approach - Balla, J. I.; Elstein, A. S. (Methods of Information in Medicine, 1984)
We demonstrate the value of skull x-rays in the assessment of head injured patients. With the use of the simple decision analytic technique of 2 x 2 tables and literature derived figures, it is shown that in patients with a normal neurological examination following head injuries, skull x-rays are a cost-effective method of detecting preventable complications. The positive predictive value (PVP) of skull x-rays in these patients is. 03, in contrast to .001 of the group as a whole. Such cases should then have a CT scan to detect early cases of intracranial haematoma (ICH). The presence of abnormal neurological signs has a high PVP of .2 for complications; in these patients, skull x-rays do not improve the detection of ICH and CT scanning alone should be carried out.
Keywords: Head Injury; Decision Analysis